“"Tavorikhi Guzida – Nusratnoma" As A Historical, Literary, And Artistic Source - Surayyo Ulugbekovna Gafurova (Global Scientific Publishing, 2024)
Studying the history of each period of human society involves the invaluable works left behind by the historians of that era. Interpreting these works comprehensively and deeply on a scientific basis is one of the significant tasks facing scholars in the fields of source studies and philology. As is well known, the Uzbek language has a very long history, with various stages of development characterized by distinct linguistic features. Indeed, the developmental stage of the Uzbek language during the 15th and 16th centuries has been recognized by scholars worldwide as the "Golden Age" 1 , therefore, it is necessary to thoroughly analyze and extensively illuminate the language of every work from this period
Keywords: language; illuminate